Gene for actin is a suitable internal reference for relative RT-PCR-based expression analysis in normal and mutant 'makapuno' endosperms of coconut (Cocos nucifera L.) - Dela Cruz, Reggie Y.; Laurena, Antonio C.; Mendioro, Merlyn S.; Laude, Rita P.; Diaz, Ma. Genaleen Q. (2011)
Makapuno is an abnormal coconut with overproliferating endosperm that is softer and fluffy due to accumulation of galactomannan. To normalize the expression of the genes possibly involved in the makapuno phenomenon by semi-quantitative polymerase chain reaction (PCR), an internal control gene was determined. The gene encoding actin exhibited a uniform expression in all the samples studied. In contrast, the expression of the genes coding for glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and enolase considerably varied. Therefore, the gene for actin can be used as reference both for normal coconut and mutant makapuno solid endosperm samples at stages 5-6, 6-7 and 7-8 mo.
Keywords: Macapuno (Coconut); gene editing